2013
DOI: 10.4028/www.scientific.net/kem.581.62
|View full text |Cite
|
Sign up to set email alerts
|

Development of Assisted Filtered Cathodic Vacuum Arc Deposition of Nano-Dispersed Multi-Layered Composite Coatings on Cutting Tools

Abstract: This paper presents the results of development and application of processes for modification of various properties of working surfaces of cutting tools by condensing vapor and ion flows in assisting impulse or constant exposure to high-energy ions. The paper shows features of the technology and equipment for the formation of wear-resistant components, which modify the structure and properties of working surfaces of various edge cutting tool types in a wide range of temperatures, in order to improve tool life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…Using this concept of dual nature, functional requirements for coatings for cutting tools were derived to prove the concept of multilayer composite coatings with nanoscale structure [1,4,5,[7][8][9]. This concept of multiple nano-layered composite stipulates that the coatings should be based on two/three components structure consisting of an adhesive underlayer, intermediate layer and the outer wear-resistant layer.…”
Section: Theoretical Prerequisitementioning
confidence: 99%
See 1 more Smart Citation
“…Using this concept of dual nature, functional requirements for coatings for cutting tools were derived to prove the concept of multilayer composite coatings with nanoscale structure [1,4,5,[7][8][9]. This concept of multiple nano-layered composite stipulates that the coatings should be based on two/three components structure consisting of an adhesive underlayer, intermediate layer and the outer wear-resistant layer.…”
Section: Theoretical Prerequisitementioning
confidence: 99%
“…Such modification help to improve the tool resistance to wear and to reduce thermomechanical stresses, which, lead to a reduce wear in a wider range of operating temperature scale, [1][2][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previously carried out research [19,24,28,29,32] NMCC Zr-ZrN-(ZrCrAl)N was chosen, as it previously showed the best result in turning of steel C45 (HB 200). This optimum coating thickness was 3-4 µm.…”
Section: Theoretical Prerequisitesmentioning
confidence: 99%
“…Leading manufacturers of coated cutting tools apply several fundamentally different processes for coating deposition, and each of them has its own advantages and disadvantages [1,[2][3][4][5][6][8][9][10]. The processes of physical vapor deposition (arc PVD) are increasingly used in manufacturing of cutting tools.…”
Section: Introductionmentioning
confidence: 99%